Analisis Sistem Pengendalian Internal Atas Penerimaan Kas Dan Pengeluaran Kas Pada CV. Media Computer - Saskia Aulia; Dedy Surahman (UMSurabaya Publishing, 2023)
ABSTRACTThe purpose of this study is to find out how the internal control system for cash receipts and cash disbursements at CV. Media Computer. The theory used in this research was Mulyadi’s theory. This was a qualitative research with descriptive research type. Then, the data collection procedure was using observation, interviews, and documentation. The results of this study indicated that the overall internal control system for cash receipts and cash disbursements at CV. Media Computer is not fully in accordance with Mulyadi's theory. It is caused by there are some elements that have not been implemented by the company in accordance with the theory used. Among them are elements of the organizational structure where there are still several dual functions performed by the company. The dual function occured in the cashier, accounting, and billing. In addition to the practice, it is still found the use of cash disbursements that are not serially numbered, no rotation of positions in the company, no stamping of